Features of online ELF in research group blogs written by multilingual scholars. (August 2018) - Luzón, María-José
Highlights: The study investigates English as a Lingua Franca in research group blogs. Writing blogs in English increases the visibility of the group's research activity. Blogs display many of the non-standard language uses found in spoken academic ELF. The purpose and the intercultural nature of the interaction influence language usage. Language usage is also influenced by the digital medium.